Inequality and Suicide Mortality: A Cross-Country Study - Antonio Rodriguez (Institute for Advanced Development Studies (INESAD), 2006)
This paper tests whether economic inequality is related to suicide mortality. Using an unbalanced panel of 40 countries for the period 1947-2001 allows us to control for the effect of unobserved factors that may have an impact on suicide rates. Our results indicate that there is a statistically insignificant positive effect of inequality on the incidence of suicide. The latter result seems to be robust to a number of specification issues explored in a sensitivity analysis. Our results also suggest that female labour participation has a significant positive effect on the total (males and female) suicide rates, supporting the sociological argument that the role conflict dominates more than the role expansion. Contrary to the total and male suicide rates findings, the fertility rate matters in explaining female suicide rates. Finally, in contrast to previous studies, suicide rates were not sensitive to income levels, divorce rates and alcohol consumption.
Keywords: I12; N30; 330; Inequality; suicide; panel data; autocorrelation